Development of Geography Literacy-Based Learning Models in an Effort to Build Spatial Intelligence in Students - Yulia Permata Sari; Afdhal; Bayu Wijayanto; Lailatur Rahmi (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a geography literacy-based learning model in an effort to build spatial intelligence in junior high school students. The model was developed using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) procedure. The analysis stage found that teachers and students needed an innovative model that could connect geographical concepts with the surrounding environment. The design stage produced model tools in the form of syntax, lesson plans, student worksheets, and assessment instruments that were validated by experts with an average score of 88% (highly valid category). In the development stage, a limited trial involving 25 students showed an increase in student engagement from 62% to 82%. The implementation stage involved experiments in two classes, where the experimental class used the geographic literacy model and the control class used conventional methods. The posttest results showed that the average spatial intelligence of students in the experimental class reached 82.6 (high category), higher than the control class at 74.1 (medium category), with a significant difference (p < 0.05). The evaluation showed a 16% increase in geographic literacy skills and an 18% increase in spatial intelligence, as well as positive responses from teachers regarding the practicality of the model. These results confirm that the geography literacy-based learning model is valid, practical, and effective in improving the spatial intelligence of junior high school students.